The Archaeology of Martin's Hundred : Part 1, Interpretive Studies; Part 2, Artifact Catalog - Noël Hume, Ivor (Book collections on Project MUSE., 2016)
Martin's Hundred was a 20,000-acre tract of land in Tidewater Virginia, one of the most extensive English enterprises in the New World. Settled in 1618, all signs of its early occupation soon disappeared, leaving no trace above ground. More than three centuries later, archaeological explorations uncovered tantalizing evidence of the people who had lived, worked, and died there.